DEMOCRATIC DIALOGUE OR POLITICAL PERFORMANCE? ANALYZING ANIES' URGENCY THROUGH THE LENS OF DELIBERATIVE DEMOCRACY - Habibur Rohman, Habibur Rohman; Rizal Al Hamid (UIN Mataram, 2024)
Desak Anies, as a political initiative led by Governor Anies Baswedan, it is the focus of research within the conceptual framework of deliberative democracy, which emphasizes the importance of broad, independent, and critical public participation in the political decision-making process. Through a descriptive-analytical approach, This study investigates Desak Anies from the perspective of deliberative democracy. Data on public participation and active participation invitations from Anies Baswedan were analyzed to understand the extent to which Desak Anies reflects an independent and critical public space. Even though Desak Anies encouraging public participation, further evaluation is needed to ensure that available public spaces support open discussion, equitable inclusion of different segments of society, and in-depth consideration of diverse views. This research provides in-depth insight into the role of Desak Anies in strengthening the principles of deliberative democracy in the context of contemporary politics. In addition, the study provides a basis for further reflection and improvement in democratic public participation, affirming the importance of strengthening public spaces to support a healthy and inclusive democratic process.